(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The aim of the research is to clarify the role of service quality through its dimensions represented by (tangibility, reliability, safety, response, empathy) in tax compliance with taxpayers, i.e. performance of the duties and obligations of the taxpayer through its dimensions (registration, accounting, payment of the amount of tax), and to know For this role, a sample was taken from the taxpayers of the branches of the General Authority for Taxes spread in the governorate of Baghdad and its affiliated districts, which amount to (15) tax branches, as (215) questionnaires were distributed to know the impressions and reactions of the taxpayers regarding the level of service quality through the aforementioned dimensions. Using the statistical program (SPSS) to analyze the questionnaire data and know the statistical results. The research concluded that there is a correlation and impact relationship between the two variables of the research, as the greater the interest in developing the level of quality of services provided through its dimensions, the higher the level of tax compliance with it.